"There Is a Lot of Change Afoot": A Qualitative Study of Faculty Adaptation to Elimination of Tiered Grades With Increased Emphasis on Feedback in Core Clerkships. (February 2021) - McDonald, Jordan A.; Lai, Cindy J.; Lin, Matthew Y.C.; O'Sullivan, Patricia S.; Hauer, Karen E.
Abstract : Purpose: Medical schools responding to challenges with fairness, equity, learning environments, and student wellness have reconsidered clerkship grades. This study used the Concerns-Based Adoption Model (CBAM) to explore how faculty responded to a change in the approach to assessment from focus on grades toward focus on feedback. Method: This qualitative study used an inductive approach to analyze data from semistructured interviews with teaching faculty and education leaders at University of California, San Francisco, School of Medicine 6 months following the elimination of traditional tiered clerkship grades. Participants were recruited in 2019 using purposive sampling. Interview questions addressed participants' perceptions of the new approach to assessment and grading that emphasizes assessment for learning, including advantages and concerns. The authors analyzed data using thematic analysis informed by sensitizing concepts from CBAM. Results: Nineteen faculty participated (11 medicine, 8 surgery). Faculty expressed optimism about the impact of the change on their clinical educator roles and sought faculty development to enhance feedback and assessment skills. Perceived benefits to students addressed learning and wellness, with concern for students' motivation and professional development. Faculty shared uncertainty about their roles and larger systemic consequences involving the residency match and institutional reputation. Participants acknowledged that traditional grading is imperfect, yet felt a departure from this system represented significant culture change. Conclusions: Faculty perceptions of the assessment and grade change in 2 large departments demonstrated tensions around grading. Their descriptions of change as an ongoing process aligned with CBAM and required them to consider new approaches and perspectives. While discourse about assessment and grading frequently focuses on learners, these findings support institutional consideration of the impact of changes in assessment on teaching faculty. Abstract : Supplemental Digital Content is available in the text.